Porous aerogel adsorption material as well as preparation method and application thereof

The titanium-based ion sieve precursor is prepared by wet method and the formation of porous aerogel adsorption materials is solved, the problem of titanium-based ion sieve in large-scale applications is improved, the capture ability and structural stability of lithium are improved, and it is suitable for low lithium concentration and alkaline environments.

CN119524794APending Publication Date: 2025-02-28GANFENG LITHIUM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411701620.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In large-scale applications, existing titanium ion sieve adsorbent materials have problems such as large grain size, uneven mixing and low purity. They also lack the ability to capture lithium in low lithium concentration and alkaline environments, and the Ti dissolved loss rate is high.

Method used

Nano-scale titanium-based ion sieve precursors are prepared by wet mixing and drying, and crosslinking is combined with binder and crosslinking agent to form a porous aerogel adsorption material. The material improves structural stability and yield through two high-temperature roasting and freeze-drying processes.

Benefits of technology

It improves the lithium capture ability of titanium-based ion sieve, reduces the Ti solvent loss rate, is suitable for lithium extraction in low-concentration and alkaline environments, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524794A_ABST
    Figure CN119524794A_ABST
Patent Text Reader

Abstract

The invention provides a porous aerogel adsorption material as well as a preparation method and application thereof, and belongs to the technical field of energy materials. The preparation method comprises the following steps: mixing and drying a water-soluble lithium salt and a titanium source to obtain a nanoscale mixed material, and roasting the nanoscale mixed material to obtain a titanium-based ion sieve precursor; the preparation method comprises the following steps: mixing a titanium-based ion sieve precursor with a binder to form slurry, cross-linking in a cross-linking agent solution to form hydrogel, and freeze-drying to obtain the porous aerogel adsorption material. The titanium-based ion sieve precursor is prepared through wet mixing, drying and roasting, and the problems that raw materials are large in grain size and uneven in mixing, and the titanium-based ion sieve is low in purity can be solved; the adsorption selectivity of carboxyl and lithium in the binder is improved through electrostatic attraction; the cross-linking agent can improve the adsorption rate and reduce the surface brittleness of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy materials, and in particular to a porous aerogel adsorption material and a preparation method and application thereof. Background Art

[0002] Lithium batteries are favored by the new energy industry due to their high energy density, high voltage stability, long cycle life, fast charging, environmental friendliness, light size and weight, etc. At present, lithium is mainly extracted from lithium ore and salt lake brine to meet the demand for lithium salt. Among the proven lithium resources, salt lake brine accounts for a much larger proportion than lithium ore, which contains huge potential for lithium extraction.

[0003] Among the methods for extracting lithium from liquid lithium resources, the adsorption method is widely used in lithium extraction from salt lakes due to its advantages of simple process, good selectivity, high recovery rate, and environmental friendliness. The core of realizing the adsorption method is to prepare adsorption materials. Among the many adsorption materials, lithium ion sieves have become a research hotspot because of their unique adsorption selectivity for lithium, strong adsorption capacity, and high chemical stability. Lithium ion sieves are mainly divided into three systems: manganese-based, aluminum-based, and titanium-based ion sieves. Among them, manganese-based ion sieves have high selectivity and strong adsorption capacity for lithium, but there is a problem of high manganese dissolution rate; aluminum-based ion sieves do not consume acid during the desorption process and have good stability, but their adsorption capacity is low, and alkaline or acidic environments will destroy their structure; titanium-based ion sieves have the advantages of good chemical stability, high theoretical adsorption capacity, and low dissolution rate, and have become a hot adsorption material for lithium extraction from alkaline salt lake brine. However, the existing powdered titanium ion sieves are not conducive to large-scale application, and improper handling will cause environmental pollution. Moreover, the lithium content of domestic salt lake brine is relatively low and the magnesium-lithium ratio is relatively high, which increases the difficulty of extracting lithium from liquid lithium resources and has a high Ti dissolution rate. Summary of the invention

[0004] The purpose of the present invention is to provide a porous aerogel adsorption material and a preparation method and application thereof, so as to improve the lithium capture ability of the titanium-based ion sieve adsorption material and reduce titanium dissolution loss.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a porous aerogel adsorption material, comprising the following steps:

[0007] The water-soluble lithium salt, the titanium source and water are mixed and dried to obtain a mixed material;

[0008] The mixed material is calcined to obtain a titanium-based ion sieve precursor;

[0009] The titanium-based ion sieve precursor is mixed with a binder, water, and a porogen, and then cross-linked with a cross-linking agent to obtain a hydrogel;

[0010] The hydrogel is dried to obtain a porous aerogel adsorption material.

[0011] Preferably, the water-soluble lithium salt includes one or more of lithium hydroxide monohydrate, lithium carbonate and lithium oxalate; and the titanium source is rutile titanium dioxide or anatase titanium dioxide.

[0012] Preferably, the mass ratio of the total mass of the water-soluble lithium salt and the titanium source to water is 1:8 to 1:20; the molar ratio of the lithium element in the water-soluble lithium salt to the titanium element in the titanium source is (2.0 to 2.3):1.

[0013] Preferably, the calcination includes a first calcination and a second calcination performed sequentially, the temperature of the first calcination is 600-850°C, the time is 4-12h, and the heating rate to the first calcination temperature is 1-5°C / min;

[0014] The temperature of the second calcination is 600-850° C., the time is 2-4 hours, and the heating rate to the second calcination temperature is 1-5° C. / min.

[0015] Preferably, the binder contains carboxyl groups and includes sodium alginate; in the cross-linking step, the mass ratio of the binder, the titanium-based ion sieve precursor and water is (1-1.5):(6-10):50;

[0016] The porogen includes one or more of sodium chloride, potassium chloride and polyvinyl pyrrolidone, and the mass of the porogen is 5-60% of the mass of the binder.

[0017] Preferably, the cross-linking agent includes one or more of aluminum chloride, aluminum sulfate and aluminum nitrate; the mass of the cross-linking agent is 25-35% of the mass of the titanium-based ion sieve precursor; and the cross-linking time is 6-24 hours.

[0018] Preferably, the drying of the hydrogel comprises freezing and freeze-drying performed in sequence, wherein the freezing temperature is -20°C for 8 to 48 hours; and the freeze-drying temperature is -56°C for 8 to 16 hours.

[0019] The present invention provides a porous aerogel adsorption material prepared by the preparation method described in the above technical solution.

[0020] The present invention provides the use of the porous aerogel adsorption material described in the above technical solution in extracting lithium from salt lake brine.

[0021] Preferably, the application method comprises:

[0022] The porous aerogel adsorbent material is mixed with an ion exchanger to perform ion exchange, and the obtained adsorbent is mixed with salt lake brine to perform adsorption;

[0023] The solid-liquid ratio of the porous aerogel adsorption material to the ion exchanger is 1 g: (20-200) mL, and the ion exchange time is 4-48 h;

[0024] The adsorption temperature is 5 to 55° C., and the adsorption time is 2 to 24 hours.

[0025] The present invention wet-mixes and dries a water-soluble lithium salt and a titanium source to obtain a nano-scale mixed material, and then calcines the material twice at high temperature to obtain a titanium-based ion sieve precursor; the titanium-based ion sieve precursor is mixed with a binder having a carboxyl group into a slurry, cross-linked in a cross-linking agent solution to form a hydrogel, and then freeze-dried to obtain a porous aerogel adsorption material. The present invention uses wet mixing, drying, and secondary high-temperature calcination to prepare a titanium-based ion sieve precursor, which can solve the problems of large raw material grain size, uneven mixing, and low purity of the titanium-based ion sieve.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention utilizes a mixed method of sand milling and spray drying granulation to promote full contact between soluble lithium salt and titanium source, reduce the grain size of the material, increase the degree of reaction, improve the structural stability and yield of Li2TiO3, and can process a large amount of raw materials in a short time, which is conducive to its large-scale application; the titanium-based ion sieve precursor is prepared by two high-temperature roastings, so that the lithium source and the titanium source react fully, which is conducive to the stable formation of the crystal structure of the titanium-based ion sieve, provides active sites for capturing lithium, improves the yield, and solves the problem of low yield of the titanium-based ion sieve. In addition, in addition to the bonding effect of the carboxyl-containing binder itself, the carboxyl group and lithium therein improve the adsorption selectivity of lithium through electrostatic attraction, so that the lithium ion sieve has a higher adsorption capacity for lithium; the cross-linking agent can increase the reaction rate of the adsorption process, improve the adsorption rate, reduce the surface brittleness of the material, and improve the service life. The hydrophilic binder and the low desorption acid concentration work together to reduce the titanium dissolution rate. Therefore, the porous aerogel adsorption material prepared by the present invention not only solves the problem of large-scale application of titanium ion sieves, but also improves the lithium capture ability and reduces the Ti dissolution rate, so that the prepared porous aerogel adsorption material is suitable for low-concentration, alkaline, and slightly acidic liquid lithium resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of the mixed powder after spray drying in Example 1;

[0029] Figure 2 This is a SEM image of the titanium-based ion sieve precursor Li2TiO3 prepared in Example 1;

[0030] Figure 3 This is a scanning electron microscope image of the porous aerogel adsorption material prepared in Example 1 at a magnification of 1k;

[0031] Figure 4 This is a bar chart showing the adsorption of different ions by the LTO@SA-Al porous aerogel adsorption material prepared in Example 1 in salt lake brine. DETAILED DESCRIPTION

[0032] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0033] The present invention provides a method for preparing a porous aerogel adsorption material, comprising the following steps:

[0034] The water-soluble lithium salt, the titanium source and water are mixed and dried to obtain a mixed material;

[0035] The mixed material is calcined to obtain a titanium-based ion sieve precursor;

[0036] The titanium-based ion sieve precursor is mixed with a binder, water, and a porogen, and then cross-linked with a cross-linking agent to obtain a hydrogel;

[0037] The hydrogel is dried to obtain a porous aerogel adsorption material.

[0038] The present invention mixes and dries water-soluble lithium salt, titanium source and water to obtain a mixed material.

[0039] In the present invention, the water-soluble lithium salt preferably includes one or more of lithium hydroxide monohydrate, lithium carbonate and lithium oxalate; when the water-soluble lithium salt is two or more of the above, the present invention has no special limitation on the ratio of different types of lithium salts, and any ratio is acceptable.

[0040] In the present invention, the titanium source is preferably rutile titanium dioxide or anatase titanium dioxide.

[0041] In the present invention, the mass ratio of the total mass of the water-soluble lithium salt and the titanium source to water is preferably 1:8-1:20, more preferably 1:10-18, and further preferably 1:12-15; the molar ratio of the lithium element in the water-soluble lithium salt to the titanium element in the titanium source is (2.0-2.3):1, more preferably (2.0-2.2):1, and further preferably 2.1:1.

[0042] In the present invention, water-soluble lithium salt and titanium source are preferably added into water, stirred and mixed for 4 hours, and then wet mixed.

[0043] In the present invention, the wet mixing method is preferably ball milling and / or sand milling; the rotation speed of the sand mill is preferably 2000 r / min, and the sand milling time is preferably 2 h.

[0044] After the wet mixing, the obtained mixture is dried to obtain a mixed material; the drying method is preferably one of spray drying, blast drying, vacuum drying, and freeze drying; the present invention has no special restrictions on the drying conditions of different drying methods, and drying can be carried out according to conditions well known in the art. In an embodiment of the present invention, the raw material temperature of the spray drying is preferably 50-60°C, and the hot air temperature is preferably 250-260°C.

[0045] After obtaining the mixed material, the present invention bakes the mixed material to obtain a titanium-based ion sieve precursor.

[0046] In the present invention, the calcination includes a first calcination and a second calcination performed sequentially; the temperature of the first calcination is preferably 600-850°C, more preferably 650-800°C, further preferably 700-750°C, the time is preferably 4-12h, more preferably 6-8h, and the heating rate to the temperature of the first calcination is preferably 1-5°C / min.

[0047] After the first calcination is completed, the present invention preferably grinds or sand-mills the obtained product and then performs a second calcination; the rotation speed of the ball mill is preferably 380 r / min, and the ball milling time is preferably 1 h.

[0048] The temperature of the second calcination is preferably 600-850°C, more preferably 650-800°C, and further preferably 700-750°C, the time is preferably 2-4 hours, and the heating rate to the second calcination temperature is preferably 1-5°C / min. The calcination instruments used for the first calcination and the second calcination are independently preferably muffle furnaces or tube furnaces.

[0049] After the second calcination is completed, a titanium-based ion sieve precursor, namely nano-scale Li2TiO3, is obtained.

[0050] After obtaining the titanium-based ion sieve precursor, the present invention mixes the titanium-based ion sieve precursor with a binder, water, and a porogen, and then cross-links the mixture with a cross-linking agent to obtain a hydrogel.

[0051] In the present invention, the binder contains carboxyl groups, and the binder preferably includes sodium alginate; in the cross-linking step, the mass ratio of the binder, titanium-based ion sieve precursor and water is preferably (1-1.5):(6-10):50, and more preferably (1-1.5):(7-9):50.

[0052] In the present invention, the porogen preferably includes one or more of sodium chloride, potassium chloride and polyvinyl pyrrolidone, and the mass of the porogen is preferably 5-60% of the mass of the binder, more preferably 25-40%.

[0053] In the present invention, the cross-linking agent preferably includes one or more of aluminum chloride, aluminum sulfate and aluminum nitrate; the cross-linking agent is preferably used in the form of a cross-linking agent aqueous solution, and the mass concentration of the cross-linking agent aqueous solution is preferably 3-7%, more preferably 4-6%, and further preferably 5%; the mass of the cross-linking agent is preferably 25-35% of the mass of the titanium-based ion sieve precursor (calculated as cross-linking agent solid), more preferably 26-32%, and further preferably 29-31%.

[0054] During the cross-linking process, the metal ions in the cross-linking agent have strong electron affinity and hydrophilicity, and undergo electrochemical reactions with the binder to generate a cross-linked gel.

[0055] The present invention preferably dissolves the binder in water, adds the titanium-based ion sieve precursor, stirs, adds the porogen to the resulting mixed solution, stirs for 2 to 10 hours (more preferably 6 hours), then drips into the crosslinker aqueous solution, and crosslinks under stirring; the present invention preferably drips the crosslinker aqueous solution at a rate of 50 to 51 r / min.

[0056] In the present invention, the cross-linking temperature is preferably room temperature, and the cross-linking time is preferably 6 to 24 hours, more preferably 10 to 12 hours.

[0057] After the cross-linking is completed, the obtained product is preferably washed three times, and the reagent used for the washing is preferably a mixed solution of 25% (volume percentage) ethanol and 75% (volume percentage) pure water.

[0058] After obtaining the hydrogel, the present invention dries the hydrogel to obtain a porous aerogel adsorption material.

[0059] In the present invention, the drying of the hydrogel includes freezing and freeze drying in sequence; the freezing temperature is preferably -20°C, the time is preferably 8 to 48 hours, more preferably 16 to 24 hours; the freeze drying temperature is preferably -56°C, the time is preferably 8 to 16 hours, more preferably 10 to 12 hours. The present invention removes the water in the material directly by sublimation through freeze drying without damaging the porous structure of the particles, avoiding high temperature drying to destroy the porous structure of the particles, causing the structure to collapse, the pores to close, and reducing the specific surface area of ​​the material, which is not conducive to the performance of its adsorption performance, thereby shortening the service life and shelf life.

[0060] The present invention provides a porous aerogel adsorption material prepared by the preparation method described in the above technical solution.

[0061] The present invention provides the use of the porous aerogel adsorption material described in the above technical solution in extracting lithium from salt lake brine.

[0062] In the present invention, the application method preferably includes:

[0063] The porous aerogel adsorbent material is mixed with an ion exchanger to carry out ion exchange, and the obtained adsorbent is mixed with salt lake brine to carry out adsorption.

[0064] In the present invention, the ion exchanger is preferably hydrochloric acid, sulfuric acid or nitric acid, and the concentration of the ion exchanger is 0.05-1.0 mol / L, more preferably 0.1-0.5 mol / L; the solid-liquid ratio of the porous aerogel adsorption material to the ion exchanger is preferably 1 g: (20-200) mL, more preferably 1 g: 100 mL, and the ion exchange time is preferably 4-48 h, more preferably 24 h.

[0065] In the present invention, the Li + The content is preferably 50 to 600 mg / L, and the pH value is preferably 5.8 to 10.0, more preferably 6.5 to 9.0. The present invention has no particular limitation on the source of the salt lake brine, and it can be obtained in a manner well known in the art.

[0066] In the present invention, the ratio of the mass of the adsorbent obtained after the ion exchange to the volume of the salt lake brine is preferably 1 to 20 g / L, more preferably 10 g / L.

[0067] In the present invention, the adsorption temperature is preferably 5 to 55° C., more preferably 25° C., and the adsorption time is preferably 2 to 24 h, more preferably 3 to 12 h.

[0068] The porous aerogel adsorption material of the present invention is suitable for alkaline environments due to the material's adsorption mechanism for lithium. After the adsorption material of the present invention is ion-exchanged, the hydrogen ions on the adsorbent are exchanged with the lithium ions in the liquid lithium resource to release the hydrogen ions into the brine, and at the same time, they are neutralized with the hydroxide ions in the alkaline brine. When the pH of the brine is adjusted to keep it in an alkaline environment, the adsorption process is promoted. The porous aerogel adsorption material of the present application is suitable for slightly acidic environments. The concentration of hydrogen ions in slightly acidic salt lakes is much lower than the concentration of lithium ions, which enables the aerogel to capture lithium in the brine by exchanging hydrogen ions with lithium ions until the concentration of hydrogen ions released into the brine is higher than the concentration of lithium ions. The adsorption rate gradually decreases and is finally in an adsorption equilibrium state.

[0069] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1

[0071] 54.3g of lithium carbonate and 53.1g of rutile titanium dioxide are dissolved in 1074mL of deionized water and stirred for 4h, with a molar ratio of lithium to titanium of 2.2:1 and a mass ratio of the total mass of lithium carbonate and rutile titanium dioxide to deionized water of 1:10; the obtained mixed solution is placed in a sand mill and ground at a speed of 2000r / min for 2h; the obtained slurry is spray-dried under the conditions of a raw material temperature of 50°C and a hot air temperature of 260°C to obtain a mixed powder; the mixed powder is placed in a muffle furnace, heated to 650°C at a rate of 5°C / min and kept warm for 6h; the calcined powder is ball-milled at 380r / min for 1h; the ball-milled powder is placed in a muffle furnace, heated to 650°C at a rate of 5°C / min and kept warm for 2h to obtain Li2TiO3 powder;

[0072] 2 g of sodium alginate was dissolved in 100 mL of pure water, and 17 g of Li2TiO3 powder was added thereto, and the mixture was stirred to obtain a mixed solution; 0.8 g of sodium chloride was added to the mixed solution, and after stirring for 6 hours, a 5% aluminum chloride aqueous solution containing 5 g of aluminum chloride was dripped at 50 r / min through a peristaltic pump, and magnetic stirring was performed for 10 hours for cross-linking, and the mixture was washed three times with a mixed solution of 25% ethanol and 75% pure water by volume; the obtained hydrogel balls were frozen at -20°C for 16 hours, and after being taken out, they were quickly placed in a freeze dryer at -56°C for vacuum drying for 12 hours to obtain LTO@SA-Al porous aerogel adsorption material.

[0073] Example 2

[0074] 59g of lithium hydroxide monohydrate and 53.1g of anatase titanium dioxide are dissolved in 1345.2mL of deionized water and stirred for 4h at a molar ratio of lithium to titanium of 2.1:1 and a mass ratio of lithium hydroxide monohydrate to anatase titanium dioxide to deionized water of 1:12; the mixed solution is placed in a sand mill and ground at a speed of 2000r / min for 2h; the obtained slurry is spray-dried under the conditions of a raw material temperature of 50°C and a hot air temperature of 250°C to obtain a mixed powder; the mixed powder is placed in a tubular furnace, heated to 700°C at a rate of 5°C / min and kept warm for 8h; the calcined powder is ball-milled at 380r / min for 1h; the ball-milled powder is placed in a tubular furnace, heated to 700°C at a rate of 5°C / min and kept warm for 2h to obtain Li2TiO3 powder;

[0075] 2.5 g of sodium alginate was dissolved in 100 mL of pure water, and 15 g of Li2TiO3 powder was added thereto, and the mixture was stirred to obtain a mixed solution; 1 g of sodium chloride was added to the mixed solution, and after stirring for 6 hours, a peristaltic pump was used to drop into a 3% aluminum chloride aqueous solution containing 4 g of aluminum chloride at a mass concentration of 50 r / min, and magnetic stirring was performed for 12 hours for cross-linking, and the mixture was washed three times with a mixed solution of 25% ethanol and 75% pure water by volume; the obtained hydrogel balls were frozen at -20°C for 12 hours, and after being taken out, they were quickly placed in a freeze dryer at -56°C for vacuum drying for 10 hours to obtain LTO@SA-Al porous aerogel adsorption material.

[0076] Example 3

[0077] 61.7g of lithium hydroxide monohydrate and 53.1g of rutile titanium dioxide are dissolved in 1722mL of deionized water and stirred for 4h, with a molar ratio of lithium to titanium of 2.2:1 and a mass ratio of lithium hydroxide monohydrate to rutile titanium dioxide to deionized water of 1:15; the obtained mixed solution is placed in a sand mill and ground at a speed of 2000r / min for 2h; the above slurry is spray-dried under the conditions of a raw material temperature of 50°C and a hot air temperature of 250°C to obtain a mixed powder; the mixed powder is placed in a muffle furnace, heated to 650°C at a rate of 5°C / min and kept warm for 12h; the calcined powder is ball-milled at 380r / min for 1h; the ball-milled powder is placed in a muffle furnace, heated to 650°C at a rate of 5°C / min and kept warm for 2h to obtain Li2TiO3 powder;

[0078] 2 g of sodium alginate was dissolved in 100 mL of pure water, and 18 g of Li2TiO3 powder was added thereto, and the mixture was stirred to obtain a mixed solution; 0.5 g of sodium chloride was added to the mixed solution, and after stirring for 6 hours, a peristaltic pump was used to drop into a 6% aluminum chloride aqueous solution containing 4.5 g of aluminum chloride at a mass concentration of 51 r / min, and magnetic stirring was performed for 10 hours for cross-linking, and the mixture was washed three times with a mixed solution of 25% ethanol and 75% pure water by volume; the obtained hydrogel balls were frozen at -20°C for 16 hours, and after being taken out, they were quickly placed in a freeze dryer at -56°C for vacuum drying for 12 hours to obtain LTO@SA-Al porous aerogel adsorption material.

[0079] Example 4

[0080] 56.5g of lithium carbonate and 53.1g of anatase titanium dioxide are dissolved in 2093.4mL of deionized water and stirred for 4h, with a molar ratio of lithium to titanium of 2.3:1 and a mass ratio of the total mass of lithium carbonate and anatase titanium dioxide to deionized water of 1:18; the obtained mixed solution is placed in a sand mill and ground at a speed of 2000r / min for 2h; the obtained slurry is spray-dried under the conditions of a raw material temperature of 50°C and a hot air temperature of 260°C to obtain a mixed powder; the mixed powder is placed in a muffle furnace, heated to 750°C at a rate of 5°C / min and kept warm for 6h; the calcined powder is ball-milled at 380r / min for 1h; the ball-milled powder is placed in a muffle furnace, heated to 750°C at a rate of 5°C / min and kept warm for 2h to obtain Li2TiO3 powder;

[0081] 3 g of sodium alginate was dissolved in 100 mL of pure water, 13 g of Li2TiO3 powder was added thereto, and the mixture was stirred evenly to obtain a mixed solution; 0.8 g of sodium chloride was added to the mixed solution, and after stirring for 6 hours, a 4% aluminum chloride aqueous solution containing 4 g of aluminum chloride was dripped into the mixed solution at 51 r / min through a peristaltic pump, and magnetic stirring was performed for 12 hours for cross-linking, and the mixed solution was washed three times with a mixed solution of 25% ethanol and 75% pure water by volume; the obtained hydrogel balls were frozen at -20°C for 24 hours, taken out and quickly placed in a freeze dryer at -56°C for vacuum drying for 12 hours to obtain LTO@SA-Al porous aerogel adsorption material.

[0082] Characterization

[0083] Figure 1 is a SEM image of the mixed powder after spray drying in Example 1, as shown Figure 1 As shown, the raw materials are mixed relatively evenly.

[0084] Figure 2 This is the SEM image of the Li2TiO3 powder prepared in Example 1. The grain size is calculated to be between 16.2 and 19.0 nm using the Scherrer formula. It can be analyzed that the prepared precursor Li2TiO3 is a nano-scale material with uniform particle size distribution.

[0085] Figure 3 This is a scanning electron microscope image of the porous aerogel adsorption material prepared in Example 1 at a magnification of 1k; Figure 3 As shown, the material surface has a porous structure.

[0086] Test Example 1

[0087] Low concentration alkaline brine test:

[0088] The LTO@SA-Al porous aerogel adsorption materials prepared in Examples 1 to 4 were acidified and tested for adsorption performance.2+ and Li + The concentration and magnesium-lithium ratio are shown in Table 1.

[0089] 5 g of the adsorbent material prepared in Examples 1 to 4 were weighed and placed in 500 mL of 0.1 mol / L sulfuric acid solution, and acidified at 500 r / min for 24 h. 2 g of the acidified HTO@SA-Al adsorbent material was weighed and placed in 200 mL of salt lake brine with an initial pH of 9, and adsorbed at 500 r / min for 3 h at 25°C. The acidification and adsorption data are shown in Table 2.

[0090] Table 1A Composition of salt lake brine

[0091]

[0092] Table 2 Acidification and lithium adsorption data of adsorbent materials prepared in Examples 1 to 4

[0093]

[0094] The saturated adsorption of the acidified LTO@SA-Al porous aerogel adsorption material on salt lake brine with a magnesium-lithium ratio of 7.6 is shown in FIG. Figure 4 shown.

[0095] From Table 2 and Figure 4 It can be seen that when the lithium source is lithium hydroxide monohydrate, the prepared material has a higher lithium capture capacity than other materials. The prepared ion sieve composite adsorption material has a much higher adsorption capacity for lithium ions than other cations in brine, indicating that it has a higher adsorption selectivity for lithium ions.

[0096] Test Example 2

[0097] Low concentration acidic brine test:

[0098] The LTO@SA-Al porous aerogel adsorption materials prepared in Examples 1 to 4 were acidified and tested for adsorption performance. 2+ and Li + The concentration and magnesium-lithium ratio are shown in Table 3.

[0099] 5 g of the adsorbent material prepared in Examples 1 to 4 were weighed and placed in 500 mL of 0.1 mol / L sulfuric acid solution, and acidified at 500 r / min for 24 h. 2 g of the acidified HTO@SA-Al adsorbent material was weighed and placed in 200 mL of salt lake brine with an initial pH of 5.8, and adsorbed at 500 r / min for 3 h at 25°C. The acidification and adsorption data are shown in Table 4.

[0100] Table 3B Composition of salt lake brine

[0101]

[0102] Table 4 Acidification and lithium adsorption data of adsorbent materials prepared in Examples 1 to 4

[0103]

[0104] It can be seen from Table 4 that the porous aerogel adsorption material prepared in the present invention is able to capture lithium in low-concentration, slightly acidic liquid lithium resources and is not limited by the high magnesium-to-lithium ratio condition.

[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous aerogel adsorption material, characterized in that: The following steps are involved: The water-soluble lithium salt, the titanium source and water are mixed and dried to obtain a mixed material; The mixed material is calcined to obtain a titanium-based ion sieve precursor; The titanium-based ion sieve precursor is mixed with a binder, water, and a porogen, and then cross-linked with a cross-linking agent to obtain a hydrogel; The hydrogel is dried to obtain a porous aerogel adsorption material.

2. The preparation method according to claim 1, characterized in that: The water-soluble lithium salt includes one or more of lithium hydroxide monohydrate, lithium carbonate and lithium oxalate; the titanium source is rutile titanium dioxide or anatase titanium dioxide.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the total mass of the water-soluble lithium salt and the titanium source to water is 1:8 to 1:20; the molar ratio of the lithium element in the water-soluble lithium salt to the titanium element in the titanium source is (2.0 to 2.3):

1.

4. The preparation method according to claim 1, characterized in that: The calcination includes a first calcination and a second calcination performed sequentially, wherein the temperature of the first calcination is 600-850°C, the time is 4-12 hours, and the heating rate to the first calcination temperature is 1-5°C / min; The temperature of the second calcination is 600-850° C., the time is 2-4 hours, and the heating rate to the second calcination temperature is 1-5° C. / min.

5. The preparation method according to claim 1, characterized in that: The binder contains carboxyl groups and includes sodium alginate; in the cross-linking step, the mass ratio of the binder, the titanium-based ion sieve precursor and water is (1-1.5):(6-10):50; The porogen includes one or more of sodium chloride, potassium chloride and polyvinyl pyrrolidone, and the mass of the porogen is 5-60% of the mass of the binder.

6. The preparation method according to claim 1, characterized in that: The cross-linking agent includes one or more of aluminum chloride, aluminum sulfate and aluminum nitrate; the mass of the cross-linking agent is 25-35% of the mass of the titanium-based ion sieve precursor; and the cross-linking time is 6-24 hours.

7. The preparation method according to claim 1, characterized in that: The drying of the hydrogel includes freezing and freeze drying performed in sequence, wherein the freezing temperature is -20°C and the time is 8 to 48 hours; and the freeze drying temperature is -56°C and the time is 8 to 16 hours.

8. The porous aerogel adsorption material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the porous aerogel adsorption material according to claim 8 in extracting lithium from salt lake brine.

10. The use according to claim 9, characterized in that: The method of application includes: The porous aerogel adsorbent material is mixed with an ion exchanger to perform ion exchange, and the obtained adsorbent is mixed with salt lake brine to perform adsorption; The solid-liquid ratio of the porous aerogel adsorbent to the ion exchanger is 1 g: (20-200) mL, and the ion exchange time is 4-48 h; The adsorption temperature is 5 to 55° C., and the adsorption time is 2 to 24 hours.